Y a-t-il un « danger écologique » ? - Quentin Hardy; Pierre de Jouvancourt (Socio, 2019)
2018 will probably be regarded as a year marking a breach in the media and popular reception of climate change: some ecological issues benefitted from a wider and relatively more demanding audience given the issues which they raised—even if huge political problems remain. In the preceding period, from the turn of the century and up until today, considerable confusion reigned around ecology, whether it be in public opinion or in part of the academic world and in the press. A close look at the speeches of several influential press “intellectuals” whose discourse repeatedly discredits ecology is instructive. This analysis helps us to understand why these issues have been relegated to the background for so long and to demonstrate the extent to which these authors value a society based on the principle of infinite innovation and technological disruption.